Resources Estimation on further Exploration activities in PT. Trimegah Bangun Persada (Harita Group) Kawasi Village, South Halmahera District, North Maluku - Talaohu, Simela; Fanani, Yazid; Putri, Fairus Atika Redanto (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2021)
PT. Trimegah Bangun Persada intends to do mining activity at the north part of IUP as the south and west parts have already been mined. This research aimed at producing natural resources of laterite nickel in the advanced exploration activity of Tangkuban Block. Besides, it also compared and determined the estimation methods having a good correlation with drilling results. Tangkuban Block carried out core drilling within total drill numbers of 286 spots and space distance 25 meters at the block area 22.16 Ha. This research began with determining the geological domain consisting of limonite, saprolite, and bedrock through a geo-statistical approach. After that, the researcher estimated nickel resources by three methods namely ordinary kriging, inverse distance weight, and nearest neighbor point. The result of estimation by ordinary kriging obtained a total volume of limonite layer 1,345,313 m3 with the content average of 1%, while the total volume of saprolite layer was 1,850,000 m3 1.64%.